Antithrombin as Substrate for the Enzyme Thrombin - Seegers, Walter H.; Yoshinari, Motoyuki; Landaburu, Ricardo H. (Thrombosis and Haemostasis, 1960)
In the interaction of thrombin (Th) and antithrombin (A) the activity of both is temporarily neutralized. Later thrombin activity regenerates and antithrombin is altered (P). Thrombin inactivates antithrombin. The experiments are interpreted on the basis of the Michaelis-Menton concept: The ThA complex is quite stable and tends to form rapidly when the concentration of A is relatively high. Dissociation and formation of inactive antithrombin (P) is favored with relatively high concentrations of thrombin.